Conference report of the 2024 Antimicrobial Resistance Meeting - Chong, CE; Pham, TM; Carey, ME; Wee, BA; Taouk, ML; Favieres, JF; Moore, CE; Dyson, ZA; Lim, C; Brown, CL; Williamson, D; Opatowski, L; et al. (Springer Nature [academic journals on nature.com], 2024)
The Antimicrobial Resistance - Genomes, Big Data and Emerging Technologies Conference explored key topics including measuring the burden of AMR, global public health pathogen genomics infrastructure and surveillance, translation and implementation of genomics for AMR control, use of techniques such as wastewater surveillance, mathematical and statistical modelling, and Artificial Intelligence (AI) to aid understanding of AMR. This report describes research presented during plenary sessions and discussions, keynote presentations and posters.